2020
DOI: 10.1186/s12985-020-01460-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for high-level BK viruria: a single center study in China

Abstract: Background BK virus allograft nephropathy is a serious complication after kidney transplantation, and the effect of pre-emptive intervention for high-level BK viruria has been verified, but protocols after kidney transplantation for early identification of high-level viruria are lacking. Methods This was a single-center study. The clinical data of the kidney transplant recipients and their donors in our center from January 1, 2015 to December 31, 2018, were collected. The patients were divided into the high-l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(19 reference statements)
1
2
0
1
Order By: Relevance
“…As with the studies performed in other centers, the incidence of BK viruria in our center was the highest within six months after surgery; we then observed a downwards trend, with an increased incidence two years after surgery (22,23). Currently, there is no speci c antiviral therapy for BKV-related diseases.…”
Section: Discussionsupporting
confidence: 83%
“…As with the studies performed in other centers, the incidence of BK viruria in our center was the highest within six months after surgery; we then observed a downwards trend, with an increased incidence two years after surgery (22,23). Currently, there is no speci c antiviral therapy for BKV-related diseases.…”
Section: Discussionsupporting
confidence: 83%
“…Many clinical studies have reported risk factors for BKVAN. Representative risk factors are renal transplantation from deceased donors, episodes of acute rejection, and Tacrolimus and/or MMF-based maintenance immunosuppression [ 17 , 18 ]. In addition, several factors associated with donors, recipients, and others have been proposed as promoting a high risk of BKVAN development ( Table 1 ).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Several studies have explored the relevant static factors of BKV replication in renal transplant recipients with inconsistent results (8)(9)(10)(11)(12)(13)(14)(15)(16); in particular, the effect of immunosuppressive regimens on BKV replication remains controversial. For example, rapamycin (mTOR) inhibitors could inhibit BKV replication, whereas tacrolimus has the opposite effect, according to the research of Hirsch et al (14).…”
Section: Introductionmentioning
confidence: 99%